2011
DOI: 10.1136/thx.2010.151522
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory features distinguishing pandemic H1N1 influenza-related pneumonia from interpandemic community-acquired pneumonia in adults

Abstract: BackgroundEarly identification of patients with H1N1 influenza-related pneumonia is desirable for the early instigation of antiviral agents. A study was undertaken to investigate whether adults admitted to hospital with H1N1 influenza-related pneumonia could be distinguished clinically from patients with non-H1N1 community-acquired pneumonia (CAP).MethodsBetween May 2009 and January 2010, clinical and epidemiological data of patients with confirmed H1N1 influenza infection admitted to 75 hospitals in the UK we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…In addition, 10-30% of hospitalized patients required admission to ICUs and mechanical ventilation. (3,6,7) Radiographic findings were similar to those seen in cases of severe pneumonia. (4,8) Viral specimens from the lower respiratory tract (BAL fluid samples) are more reliable than are those of samples from the upper airway.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…In addition, 10-30% of hospitalized patients required admission to ICUs and mechanical ventilation. (3,6,7) Radiographic findings were similar to those seen in cases of severe pneumonia. (4,8) Viral specimens from the lower respiratory tract (BAL fluid samples) are more reliable than are those of samples from the upper airway.…”
Section: Introductionsupporting
confidence: 66%
“…(12,13) Higher Acute Physiology and Chronic Health Evaluation II (APACHE II) scores, lower PaO 2 /FiO 2 ratio, shock, hemodialysis, and Streptococcus pneumoniae infection are independent factors predicting death. (6,7,10,14) From the beginning of the epidemic, influenza A (H1N1) infection seemed to have a more severe course and worse outcomes than did infection with seasonal influenza A. In addition, the demographic profile of influenza A (H1N1) infection was younger, and it affected individuals with fewer comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…and Franquet,21, 22 unless a formal radiograph report also stated ‘no pneumonia’.Chest radiograph report not provided, but specific mention in the clinical case notes that a radiograph had been formally reported as showing pneumonia. …”
Section: Methodsmentioning
confidence: 99%
“…Unlike seasonal influenza, seen in previous years, thrombocytopenia have been experienced in pandemic (H 1 N 1 ) influenza-A in some studies from Turkey and internationally (3,12,(16)(17)(18)(19). Leukopenia and lymphopenia, which is an indicator of viral infection, is a common finding in pandemic (H 1 N 1 ) influenza-A pneumonia (3,15). Cunha et al (20) have shown that lymphopenia, and thrombocytopenia may play a key role in the diagnosis of pandemic (H 1 N 1 ) influenza-A pneumonia in hospitalized cases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mortality rate may differ in ICU patients and was reported to vary between 15% and 62.5% according to the centers (4,23,24). However, in some studies, the mortality rate of pandemic (H 1 N 1 ) influenza-A pneumonia cases not requiring ICU support did not differ from that of CAP with no H 1 N 1 infection (3,15).…”
Section: H1n1mentioning
confidence: 99%